Decline and recovery of pelagic acoustic backscatter following El Niño events in the Gulf of California, Mexico. (August 2022) - Portner, Elan J.; Benoit-Bird, Kelly J.; Hazen, Elliott L.; Waluk, Chad M.; Robinson, Carlos J.; Gómez-Gutiérrez, Jaime; Gilly, William F.
Highlights: Timeseries of acoustic backscatter as a proxy for midtrophic biomass in the Gulf of California. ENSO explained more variability than regional temperature or chlorophyll concentration. Backscatter decreased significantly during the positive phase of ENSO (El Niño). Mean backscatter took more than two years to recover to pre-El Niño levels. Abstract: Climatic variability exerts enormous pressures on the structure and function of open ocean ecosystems. Although the responses of primary producers and top predators to these pressures are being increasingly well-documented, little is known about how midtrophic communities respond to oceanographic and climatic variability. We address this knowledge gap through a study of the effects of El Niño Southern Oscillation (ENSO) and local environmental conditions on acoustic proxies of the midtrophic community in the Gulf of California, Mexico. We quantified the intensity and distribution of nighttime acoustic backscatter (120 kHz) in the upper 200 m of the water column during 10 oceanographic cruises (2007–2017) and described its response to environmental variability using generalized additive models. ENSO conditions were the strongest drivers of variability in backscatter after accounting for seasonal increases in backscatter with sea surface temperature and chlorophyll- a concentration. Acoustic backscatter in the central Gulf of California decreased significantly during the positive phase of ENSO. Following El Niño events in 2009–10 and 2015–16, mean backscatter declined by an order of magnitude and remained depressed for more than two years before recovering to pre-El Niño levels. Scattering layer density increased with total backscatter, likely an influential factor determining prey availability for pelagic predators. Our findings demonstrate large and sustained impacts of El Niño on the midtrophic community in the Gulf of California and further highlight the need to better understand the responses of midtrophic communities to environmental variability.